Anti-Inflammatory and Anti-Migratory Effects of Morin on Non-Small-Cell Lung Cancer Metastasis via Inhibition of NLRP3/MAPK Signaling Pathway - Punnida Arjsri; Kamonwan Srisawad; Sonthaya Umsumarng; Pilaiporn Thippraphan; Songyot Anuchapreeda; Pornngarm Dejkriengkraikul (Biomolecules)
Non-small-cell lung cancer (NSCLC) remains the leading cause of cancer-related deaths globally, with a persistently low five-year survival rate of only 14–17%. High rates of metastasis contribute significantly to the poor prognosis of NSCLC, in which inflammation plays an important role by enhancing tumor growth, angiogenesis, and metastasis. Targeting inflammatory pathways within cancer cells may thus represent a promising strategy for inhibiting NSCLC metastasis. This study evaluated the anti-inflammatory and anti-metastatic properties of morin, a bioactive compound derived from a Thai medicinal herb, focusing on its effects on NLRP3 inflammasome-mediated pathways in an in vitro NSCLC model. The A549 and H1299 cell lines were stimulated with lipopolysaccharide (LPS) and adenosine triphosphate (ATP) to activate the NLRP3 pathway. The inhibition effects exhibited by morin in reducing pro-inflammatory secretion in LPS- and ATP-stimulated NSCLC cells were assessed by ELISA, while wound healing and trans-well invasion assays evaluated its impact on cell migration and invasion. RT-qPCR measurement quantified the expression of inflammatory genes, and zymography and Western blotting were used to examine changes in invasive protein levels, epithelial-to-mesenchymal transition (EMT) markers, and underlying molecular mechanisms. Our findings demonstrated the significant ability of morin to decrease the production of IL-1β, IL-18, and IL-6 in a dose-dependent manner (p < 0.05), as well as suppress NSCLC cell migration and invasion. Morin downregulated invasive proteins (MMP-2, MMP-9, u-PAR, u-PA, MT1-MMP) and EMT markers (fibronectin, N-cadherin, vimentin) (p < 0.01) while also reducing the mRNA levels of NLRP3, IL-1β, IL-18, and IL-6. Mechanistic investigations revealed that morin suppressed NLRP3 inflammasome activity and inactivated MAPK pathways. Specifically, it decreased the expression of NLRP3 and ASC proteins and reduced caspase-1 activity, while reducing the phosphorylation of ERK, JNK, and p38 proteins. Collectively, these findings suggest that morin’s inactivation of the NLRP3 inflammasome pathway could offer a novel therapeutic strategy for counteracting pro-tumorigenic inflammation and metastatic progression in NSCLC.